2023
DOI: 10.1556/030.2022.01882
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of multiresistant Pseudomonas aeruginosa isolates from burn patients in Iran

Abstract: Infections caused by multidrug resistant (MDR) Pseudomonas aeruginosa isolates in burn patients restrict therapeutic strategies. The current study aimed to analyze antibiotic resistance genes and multilocus sequence typing (MLST) of P. aeruginosa strains isolated from burn patients in Shahid Motahari hospital in Tehran, Iran.Altogether 63 P. aeruginosa isolates were characterized in this study. Antibiotic susceptibility testing was performed by disc diffusion method. PCR was performed to determine the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Among the diversity of STs found in this work, the high-risk clone ST235 was encountered in two strains. ST235 has been largely reported in different other infections such as in wound infections and in burn patients [70–72] and has been associated with fatal patient outcomes [33, 73–76]. However, to the best of our knowledge, ST235 has not been previously described in DFIs, highlighting the presence and subsequent dissemination of this clone in this type of infections.…”
Section: Discussionmentioning
confidence: 94%
“…Among the diversity of STs found in this work, the high-risk clone ST235 was encountered in two strains. ST235 has been largely reported in different other infections such as in wound infections and in burn patients [70–72] and has been associated with fatal patient outcomes [33, 73–76]. However, to the best of our knowledge, ST235 has not been previously described in DFIs, highlighting the presence and subsequent dissemination of this clone in this type of infections.…”
Section: Discussionmentioning
confidence: 94%
“…Ma et al demonstrated that the psl gene plays a critical role in adherence of cell surfaces [3]. Bioflm production by P. aeruginosa facilitates its persistence in the environment and can lead to severe bacterial infections, especially in hospitalized patients [4]. However, in vitro bioflm production among clinical strains varies, and P. aeruginosa can be classifed as strong, moderate, weak, or nonbioflm producers [5,6].…”
Section: Introductionmentioning
confidence: 99%